2010
DOI: 10.1590/s0103-64402010000300005
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxicity of latex and non-latex orthodontic elastomeric ligatures on L929 mouse fibroblasts

Abstract: This study investigated the cytotoxicity exists between latex and non-latex Orthodontic elastomeric ligatures. Six elastomeric ligatures (1 latex, 2 latex-free and 3 polyurethane) from different manufacturers were divided into 6 groups of 15 elastics each: A (Latex-free, American Orthodontics), M (Polyurethane, Morelli), G (Polyurethane,GAC International), Te (Polyurethane, Tecnident), TP (Natural latex,TP Orthodontics) and U (Latex-free,3M Unitek). The cytotoxicity assay was performed using cell cultures (L92… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 20 publications
(27 reference statements)
1
21
0
1
Order By: Relevance
“…Although the acrylic resins tested by different methods presented over 50% of cell viability in all the experimental time intervals (Table 2), which does not contraindicate their clinical use, as seen in other studies (20,24) on cytotoxicity of materials (25) for use in dentistry that showed similar performance. However, the findings of this study suggest that the mass technique associated with manual polishing must be encouraged whenever possible, but the saturation technique associated with chemical polishing seems to be less suitable.…”
Section: Discussionsupporting
confidence: 69%
“…Although the acrylic resins tested by different methods presented over 50% of cell viability in all the experimental time intervals (Table 2), which does not contraindicate their clinical use, as seen in other studies (20,24) on cytotoxicity of materials (25) for use in dentistry that showed similar performance. However, the findings of this study suggest that the mass technique associated with manual polishing must be encouraged whenever possible, but the saturation technique associated with chemical polishing seems to be less suitable.…”
Section: Discussionsupporting
confidence: 69%
“…In this study, neutral red dye was used because it is widely used for identification of L-929 cell viability. 3,4 Dead or damaged cells cannot incorporate vital stain and are thus not recognized on optical reading. Therefore, spectrophotometry does not allow dead cells to be distinguished from the damaged ones.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, the elastics were superficially washed with deionized water (Millipore, Bedford, Mass) for 5 seconds and sterilized on both sides with ultraviolet light (Labconco, Kansas City, Mo) for 30 minutes. [3][4][5]18 To verify the cell response to extreme situations, another three groups were included in the study: group cell control (CC), consisting of cells not exposed to any material; group positive control (C+), consisting of Tween 80; and group (negative control (C2), consisting of phosphate-buffered saline (PBS) solution in contact with the cells.…”
Section: Cytotoxicity Testmentioning
confidence: 99%
See 1 more Smart Citation
“…Elastomeric chains have been widely used in Orthodontics since the 1960s and its effects has been evaluated since then (1)(2)(3)(4)(5). They are used to deliver continuous light forces during sliding mechanics in diastema closure (6), rotational correction, and mainly during canine retraction after premolar extraction (7,8).…”
Section: Introductionmentioning
confidence: 99%